2016
DOI: 10.3390/app6040113
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Estimation of Femoral Neck Bone Mineral Density Using Forearm Images from Peripheral Cone Beam Computed Tomography

Abstract: Abstract:The main goal of osteoporosis treatment is prevention of osteoporosis-induced bone fracture. Dual-energy X-ray absorptiometry (DXA) and quantitative computed tomographic imaging (QCT) are widely used for assessment of bone mineral density (BMD). However, they have limitations in patients with special conditions. This study evaluated a method for diagnosis of osteoporosis using peripheral cone beam computed tomography (CBCT) to estimate BMD. We investigated the correlation between the ratio of cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 29 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…In [26], bicortical thickness of the distal radius was positively correlated with femoral neck BMD. Recently, it was reported that a femoral neck BMD is associated with the relative cortical bone area of forearm [17]. All these studies reflect that the bones in forearm and hip are correlated.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In [26], bicortical thickness of the distal radius was positively correlated with femoral neck BMD. Recently, it was reported that a femoral neck BMD is associated with the relative cortical bone area of forearm [17]. All these studies reflect that the bones in forearm and hip are correlated.…”
Section: Discussionmentioning
confidence: 87%
“…In [23], a feasibility study was conducted that forearm BMD using DXA may predict hip osteoporosis. In [17,[24][25][26], the investigators showed that some parameters from the cortical bone in distal radius and ulna on anteroposterior radiograph could reflect the femoral neck BMD. In [24], the distal radius BMD was correlated with the ratio of the outside cortical shell diameter to the inside cortical shell diameter at the metaphyseal/diaphyseal junction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, assuming the CBCT detector is optimized with the corresponding thickness, the radiation dose can be further reduced up to 1/462 times, which is approximately equivalent to 0.3 µSv. Furthermore, the forearm CBCT images can be used for estimating BMD values of lumbar spine and hip bone with a linear regression (Jeong et al 2016 ). Then, for lumbar spine and/or hip bone BMD, the effective radiation dose from CBCT is less than that from DXA, 2.2 µSv (Thomas et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the advantages in our approach is that only a forearm needs to be exposed via X-ray for BMD assessment of a lumbar spine and/or hip bones since the forearm CBCT images can be used for estimating BMD values of a lumbar spine and hip bones (Jeong et al 2016 ). On the other hand, traditional approaches using DXA and QCT require X-ray exposure in the entire axial skeleton near a lumbar spine or a hip.…”
Section: Discussionmentioning
confidence: 99%